Analisis Pengaruh Kinerja Keuangan Terhadap Nilai Perusahaan (Studi Kasus pada Perusahaan Farmasi yang terdaftar di Bursa Efek Indonesia Periode 2017-2021) - Rizka Ariyanti; M. Iqbal Notoatmojo; Rizka Muamaroh (Jurnal Aktual Akuntansi Keuangan Bisnis Terapan (AKUNBISNIS), 2023)
ABSTRACT : This study aims to determine the effect of Return On Assets, Debt To Equity Ratio, and Current ratio, Total Asset Turnover, Inventory Turnover Ratio on Price Book Value partially and simultaneously in pharmaceutical sector manufacturing companies listed on the Indonesia Stock Exchange (IDX). The population used in this study are pharmaceutical sector manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2016-2021 period. The sample used in this study is a pharmaceutical sector manufacturing company that meets the criteria sought by researchers who are registered on the Indonesia Stock Exchange (IDX) for a 5 year period from 2017-2021. The method used to test this research is multiple linear regression analysis, partial test (t test) and simultaneous test (F test). Based on the partial test, it shows that Return on Assets, Debt To Equity Ratio, Current ratio, Total Asset Turnover, Inventory Ratio have an effect on Price Book Value.